If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 9 = -40x + -5x Reorder the terms: 9 + 2x = -40x + -5x Combine like terms: -40x + -5x = -45x 9 + 2x = -45x Solving 9 + 2x = -45x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '45x' to each side of the equation. 9 + 2x + 45x = -45x + 45x Combine like terms: 2x + 45x = 47x 9 + 47x = -45x + 45x Combine like terms: -45x + 45x = 0 9 + 47x = 0 Add '-9' to each side of the equation. 9 + -9 + 47x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 47x = 0 + -9 47x = 0 + -9 Combine like terms: 0 + -9 = -9 47x = -9 Divide each side by '47'. x = -0.1914893617 Simplifying x = -0.1914893617
| 1-3(7x-8)=8(-2x+6)-5 | | 8+7k=6k | | 8+2z=z | | 105=3(4x+3) | | 27-1/28(3x)=18-1/28(2x) | | 3x(6x+7)= | | 3y^2-8y-5=0 | | 1/2(z+1/8)=-1/6(z+1/8) | | -4(4a-3)= | | -198=-6(14a) | | 4+10x=-41+x | | v-5/7v-1/6=4/3(v-5/7) | | 35-x=24 | | 6m+14x=100 | | 368=-8(6n-4) | | 9x-2=39+3x | | -8(2x^2+3m)= | | (x+y)+x=6 | | -4b+11b=-7 | | 2.7(x-1)=0.5(x-12) | | 8x-4y=100 | | 6(4-6d)= | | 6a+5(2+8a)=378 | | -6(-7-5m^2)= | | -124=2(2-8k) | | 2(8d-6)= | | -4(1+4p)=108 | | -42+3x=12-3 | | -9(-2-5)= | | 3(6m+9)= | | -5(8x-3)=-225 | | 3x+g+2h=t-y |